Ferroptosis: Mechanism and connections with cutaneous diseases - Liu, Lihao; Lian, Ni; Shi, Liqing; Hao, Zhimin; Chen, Kun (Frontiers in Cell and Developmental Biology, 2023)
Ferroptosis is a recognized novel form of programmed cell death pathway, featuring abnormalities in iron metabolism, SystemXc-/glutathione axis, and lipid peroxidation regulation. A variety of ferroptosis inducers can influence glutathione peroxidase directly or indirectly via diverse pathways, leading to decreased antioxidant capacity, accumulated cellular lipid peroxides, and finally inducing ferroptosis. To date, mounting studies confirm the association of ferroptosis with various cutaneous diseases, including skin homeostasis, neoplastic diseases, infectious diseases, genetic skin disease, inflammatory skin diseases, and autoimmune diseases. There are shared characteristics regarding ferroptosis and various cutaneous diseases in terms of pathophysiological mechanisms, such as oxidative stress associated with iron metabolism disorder and accumulated lipid peroxides. Therefore, we summarize the current knowledge regarding the mechanisms involved in the regulation of ferroptosis for further discussion of its role in the pathogenesis and prognosis of skin diseases. Gaining insight into the underlying mechanisms of ferroptosis and the associated dermatological disorders could illuminate the pathogenesis and treatments of different cutaneous diseases.